Factors influencing acceptance of ar-rahnu: a study between customers in Bank Rakyat Perak and quantitative structure / Nor Syafiqah Che Umar - Che Umar, Nor Syafiqah (2021)
The introduction of Islamic pawn broking (al-Rahnu) in Malaysia has seen as a new micro credit instrument in providing cash borrowing facility to lower income communities. The Muslims individuals’ especially needy people are reliant on this institution as their financial resources and necessities fulfillment. Al-Rahnu as well as reflected to Islamic business operation are must conducted according to Shari’ah principles whereas the process transaction is must show transparent and free of ambiguity and element of riba. Thus, it is important to have a study of Ar-Rahnu practice in Islamic finance industry as the Muslim communities have put trusted to the system institution, in fact, the number of demands in Ar-Rahnu has shown increased by over the years until present. In an attempt to fulfill the aims of the research study, the interview will be conducted to selected institution cooperatives. This study will be given a focus to factors influencing acceptance of ar-rahnu among customers in Bank Rakyat. This will describe an overview of Islamic pawn broking (al-Rahnu) concepts and analyze its actual modus operation implemented by cooperatives. Nevertheless, by conduct a study of Ar-Rahnu scheme according Shari’ah framework theory and the challenges, perhaps we might get a clear clarification of al-Rahnu practice in cooperative and be useful for the businesses and government in considering the future development related to Ar-Rahnu pawnshops. Now, the rising cost of living and the strict banking act about financing procedure causes Ar-Rahnu is one of the alternative ways for those on low incomes to borrow money easily and quickly without incurring any high profit rate. This study aims to knowing the factors of customers to use Ar-Rahnu in Bank Rakyat Perak. A survey of 130 respondents was conducted. Next that is, the use of shariah views, attitudes, prices and customer service as a factor will help researchers to know the factors that most influence customers to use Ar-Rahnu.